Youth Teachers Program in Information Technology Management - Sunu, I Gusti Ketut Arya (Universitas Pendidikan Ganesha, 2022)
Quality management is a tool that allows teachers to adapt to the forces of change hitting the education system, the knowledge needed to improve our education system already exists within the education community itself. The main difficulty faced by teachers today is their inability to deal with the new system so that it becomes a problem for teachers to develop or implement new educational processes that will improve the quality of education. This study aims to analyze the results of independent and simultaneous evaluations in terms of context, input, process, product, and the constraints in the Young Teacher Training program in the management of information and communication technology. This research was a program evaluation research with the CIPP model. The population of this study was 69 educators and administrative staff. The samples of the study were selected using a random sampling technique. Data regarding context, input, process, and product in this study were collected using a questionnaire using a Likert scale of 1-5. The data analysis method used in this research is the quantitative descriptive analysis method. The analysis found that the Young Teachers' Program in managing information technology has proven to be effective in terms of context, input, process, and product, both independently and simultaneously. However, some technical and non-technical obstacles are still experienced during program implementation.